EFEKTIVITAS KONSULTASI GIZI TERHADAP PENGETAHUAN, SIKAP, POLA MAKAN DAN TEKANAN DARAH PENDERITA HIPERTENSI DI POLI GIZI RSUD PROVINSI SULBAR - Bahirah Bahirah; Suherman Rate; Kurnia Yusuf (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2022)
Hypertension can be defined as blood pressure that exceeds 140/90 mmHg. Factors that decrease blood pressure can be caused by several things, including diet, knowledge and patient attitudes. The purpose of this study was to determine the effectiveness of nutrition consultation on blood pressure, knowledge, attitudes and eating patterns of hypertension sufferers at the Nutrition Poly Hospital of West Sulawesi Province. The research method used is Pre Experimental Designs using the One Group Pretest - Posttest design. The research was carried out in the Nutrition Poly Room of the West Sulawesi Provincial Hospital from August 2021 to October 2021. The number of samples in this study was set at 33 people determined by the Cross Sectional sample formula. The results showed that before the nutrition consultation, 100% of respondents had hypertension, 10% of respondents had low knowledge, 69.7% of respondents were negative and 57.5% of respondents had a poor diet. After the nutrition consultation for hypertension patients was reduced to 10%, knowledge increased 93.4%, respondents had a positive attitude increased by 87.9, while the diet of 60.7% respondents was effective in reducing blood pressure, increasing knowledge, changing respondents' attitudes and eating patterns. respondents (p<0.05),. It can be said that the provision of nutrition consultation to patients with hypertension has an impact on increasing behavioral changes from hypertension sufferers who visit the nutrition polyclinic of the West Sulawesi Provincial Hospital.